The measurement of time and income poverty - Ajit Zacharias (Levy Economics Institute of Bard College, 2011)
Official poverty thresholds are based on the implicit assumption that the household with poverty-level income possesses sufficient time for household production to enable it to reproduce itself as a unit. Several authors have questioned the validity of the assumption and explored alternative methods to account for time deficits in the measurement of poverty. I critically review the alternative approaches within a unified framework to highlight the commonalities and relative merits of individual approaches. I also propose a two-dimensional, time-income poverty measure that accounts for intrahousehold disparities in the division of household labor and briefly discuss its uses in thinking about antipoverty policies.
Keywords: B54; I32; J16; J22; 330; time poverty; household production; gender disparities